1993
DOI: 10.1002/app.1993.070490601
|View full text |Cite
|
Sign up to set email alerts
|

Graft copolymers of wood pulp and 1‐phenylethene. I. Generality of synthesis and proof of copolymerization

Abstract: A method of grafting lignin‐containing materials is now known that allows 1‐phenylethylene (styrene, [100‐42‐5]) graft copolymers of a lignin source to be quantitatively made. The grafting reaction is a solution polymerization often run in aprotic, polar, organic solvents. Grafting changes solubility and surface properties of the lignin‐containing material. The lignin‐containing materials grafted are unbleached wood pulps produced by chemical, thermal, and mechanical pulping. Grafting wood pulp produces a wood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There are many papers regarding grafting of synthetic vinyl monomers like styrene, acrylamide, acrylonitrile onto lignin or hemicellulose by free radical copolymerization in chemical initiation of radicals (Phillips et al 1972;Fanta et al 1982;Meister et al 1984Meister et al , 1991Meister and Patil 1985;Meister and Chen 1993) or chemoenzymatical (Milstein et al 1989;Milstein et al 1993Milstein et al , 1994Mai et al 2000). There are also reports on free radicals generation using high-frequency ultrasound (Petrier et al 1994;Gadhe et al 2006), UV laser energy (Dodson et al 2009), or cirradiation (Supe et al 1993) which, in fact, are a combination of physical and chemical modification.…”
Section: Introductionmentioning
confidence: 99%
“…There are many papers regarding grafting of synthetic vinyl monomers like styrene, acrylamide, acrylonitrile onto lignin or hemicellulose by free radical copolymerization in chemical initiation of radicals (Phillips et al 1972;Fanta et al 1982;Meister et al 1984Meister et al , 1991Meister and Patil 1985;Meister and Chen 1993) or chemoenzymatical (Milstein et al 1989;Milstein et al 1993Milstein et al , 1994Mai et al 2000). There are also reports on free radicals generation using high-frequency ultrasound (Petrier et al 1994;Gadhe et al 2006), UV laser energy (Dodson et al 2009), or cirradiation (Supe et al 1993) which, in fact, are a combination of physical and chemical modification.…”
Section: Introductionmentioning
confidence: 99%
“…Meister et al have shown that when lignin is reacted with 2‐propaneamide and 2,2‐dimethyl‐3‐amino‐4‐oxohex‐5‐ene‐1‐sulfonic acid it forms a graft terpolymer that is water soluble 15. Meister et al has also shown that lignin can be synthesized with 2‐propenamide as well as 1‐phenylethylene to form graft copolymers with lignin 16–20. Jo and coworkers have shown that aniline can be reacted with poly(styrenesulfonic acid‐ co ‐aminostyrene) also resulting in a copolymer with improved solubility 21.…”
Section: Introductionmentioning
confidence: 99%
“…16 Several researchers have also reported the successful grafting of lignin, which has a structure similar to tannin, to various copolymers. [17][18][19][20][21][22] Additionally, Joseph and coworkers have demonstrated that polymers formed via free radical mechanisms can be covalently grafted to tannins, resulting in a homogenous dispersion of the polymer in water. 23 Possible sites of grafting polyaniline to the TS are indicated by an asterisk in Figure 1.…”
Section: Introductionmentioning
confidence: 99%